قراءة في ميميَّة المتنبي - عيسى حكمت إبراهيم (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يتناول البحث نصاً شعرياً لشاعر العربية المتنبي، محاولاً استجلاء المعنى الشمولي للنص، بعلاقته مع الذات المبدعة معتمداً على أدوات معرفية أفرزتها المناهج النقدية المتنوعة، والتي تتفق على أن العمل الشعري الشائك في إبداعه يستدعي من القارئ والناقد جهداً موازياً، يستنهض من خلاله معارفه للكشف عن كنه المعنى الشعري وخصوصياته فبعد أن غدت الدراسة الكلية للنص من أهم معالم الحركة النقدية المعاصرة، أضحى من الضرورة التعامل مع النصوص التراثية، باعتبارها وحدة بنائية متكاملة، بعد أن كان ينظر إليها كأجزاء مبعثرة ساهمت في عزل النص عن التجربة المعيشة والخلاقة. يجتهد البحث في تقديم قراءة كلية للنص المعني بالدراسة، معتمداً على تأملات تبتعد عن الاستنتاجات والأفكار المسبقة This study tackles a major poetic text by al-Mutanabi, the quint essential Arab poet and bard. It seeks to decipher and clarify the totality of the meaning in relation to the creative poetic self, depending on various epistemological tools of various critical methodologies. All these contemporary critical methodologies concede the fact that the “ difficult, problematic and dense poetic text necessitates, from reader and critic alike, a parallel effort tapping all her/his cognitive faculties to detect its essential creative meaning and peculiarities. This unitary study of the text has become a major feature of the contemporary critical approach to literature. There is consequently a quid pro quo demand nowadays to look at the classical poetic text as a comprehensive unitary structure rather than a composite of fragmentary parts, isolating the text from the reality and the totality of lived, creative life. The study endeavours to offer a unitary of the mentioned text, relying on fresh insights abandoning all preconceived ideas and conclusions.